2012
DOI: 10.1016/j.jtcvs.2012.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of sternal wound infections in diabetic patients undergoing off-pump coronary artery bypass surgery and using modified pedicle bilateral internal thoracic artery harvest technique

Abstract: Objective: We compared sternal wound infections between diabetic patients undergoing off-pump coronary artery bypass surgery using bilateral internal thoracic artery grafting or single internal thoracic artery grafting and nondiabetic patients receiving bilateral internal thoracic artery or single internal thoracic artery grafting using a modified pedicled harvest technique of internal thoracic artery.Methods: This retrospective study was conducted to analyze the data from 3072 patients who underwent primary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Sparing of the communicating bifurcation of the ITA to the chest wall and preservation of pericardiacophrenic artery branch has been reported to minimize the risk of sternal wound complication in patients receiving P-BITA. 23 In the present study, we could not confirm this hypothesis because data on technical aspects of harvesting technique were not reported. OR, Odds ratio; CI, confidence interval; LL, lower limit; UL, upper limit; P-BITA, pedicled bilateral internal thoracic artery; P-SITA, pedicled single internal thoracic artery; S-SITA, skeletonized single internal thoracic artery; S-BITA, skeletonized bilateral internal thoracic artery; BMI, body mass index; NYHA, New York Heart Association; COPD, chronic obstructive pulmonary disease; PVD, peripheral vascular disease; MI, myocardial infarction; LVEF, left ventricular ejection fraction.…”
Section: Study Limitationsmentioning
confidence: 61%
“…Sparing of the communicating bifurcation of the ITA to the chest wall and preservation of pericardiacophrenic artery branch has been reported to minimize the risk of sternal wound complication in patients receiving P-BITA. 23 In the present study, we could not confirm this hypothesis because data on technical aspects of harvesting technique were not reported. OR, Odds ratio; CI, confidence interval; LL, lower limit; UL, upper limit; P-BITA, pedicled bilateral internal thoracic artery; P-SITA, pedicled single internal thoracic artery; S-SITA, skeletonized single internal thoracic artery; S-BITA, skeletonized bilateral internal thoracic artery; BMI, body mass index; NYHA, New York Heart Association; COPD, chronic obstructive pulmonary disease; PVD, peripheral vascular disease; MI, myocardial infarction; LVEF, left ventricular ejection fraction.…”
Section: Study Limitationsmentioning
confidence: 61%
“…Previous observational studies have reported that the incidence of DSWI following BIMA harvest ranged from 0.6% to 4.2%. 23,24) Recently, a meta-analysis has reported that the incidence of DSWI after BIMA grafting ranged widely from 0.3% to as high as 14%. 25) In the ART, the rate of sternal wound infection was 3.5% for BIMA harvest.…”
Section: Discussionmentioning
confidence: 99%
“…This result agreed with the results of the overwhelming majority of previous studies. 4,5,7,19,[23][24][25][26] Results from this study showed that compared with skeletonized SIMA harvest, skeletonized BIMA harvest did not increase the risk of sternal wound complications regardless of whether or not the merger with diabetes and compared with skeletonized SIMA grafting, skeletonized BIMA grafting did not increase the risks of surgical mortality or major postoperative morbidity. This study serves as additional confirmation and a reminder that the time is right to change our old habits and to adopt a skeletonized approach as the standard technique for IMA harvesting.…”
Section: Impacts Of Bima Grafting On the Risk Of Dswimentioning
confidence: 99%
“…Sajja LR, et al [18] found that average age of the patient was 57.8 ± 7.43 years. Omran AS, et al [14] demonstrated that the average age of the patient was 58.5 ± 9.7 years.…”
Section: Discussionmentioning
confidence: 95%